2001
DOI: 10.1142/s0218810401000394
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Subungual Glomus Tumour

Abstract: We reviewed 30 patients with subungual glomus tumours of the hand operated on between 1964 and 1997. Seven patients were male and 23 were female. Their age ranged from 16 to 78 years. A transungual approach was selected in 27 patients, and a periungual approach in three. Pre-operative pain subsided in all of the patients, but recurrence of the pain was observed in nine. Nail deformities were observed in nine patients before surgery. After surgery, it disappeared in three patients, persisted in six, and new def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 7 publications
3
35
1
8
Order By: Relevance
“…4,19 The anatomic distribution of glomus tumor was relatively similar to other studies, with the vast majority in the dermis and subcutis. In particular, the digits, distal upper extremities, and lower extremities were the most common sites.…”
Section: Discussionsupporting
confidence: 78%
“…4,19 The anatomic distribution of glomus tumor was relatively similar to other studies, with the vast majority in the dermis and subcutis. In particular, the digits, distal upper extremities, and lower extremities were the most common sites.…”
Section: Discussionsupporting
confidence: 78%
“…In our clinical practice, we have found that it is difficult to raise the nail bed on both two sides to expose the tumor because of the poor flexibility of the nail bed. In addition, this technique is indicated only for tumors located in the central subungual region and has a high rate of nail deformity …”
Section: Discussionmentioning
confidence: 99%
“…In addition, this technique is indicated only for tumors located in the central subungual region and has a high rate of nail deformity. 4,13,14 Multiple surgical methods have been proposed to avoid nail bed damage. In 1972, Carroll and Berman reported the use of a "lateral incision close to the edge of the nail" to approach subungual glomus tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Transungual approach can lead to nail deformity, thus periungual approach has been advocated in tumour in peripheral locations and transungual approach for central regions with meticulous repair of nail bed by plastic surgery. 4 We had localised the lesions preoperatively; being in the central region thus had preferred the transungual approach with nail bed reconstruction. In both cases glomus tumour was completely excised with adequate margin; no recurrence occurred in one year of follow-up period.…”
Section: Discussionmentioning
confidence: 99%